"Secret disease": Tracking syphilis through America - Phillips, Shawn (Medicina Historica, 2024)
This review essay tracks syphilis, and the medical community’s responses to the disease, from the Colonial Period through the availability of penicillin in the 20th century (1585 to 1945). The essay demonstrates physicians actively aided their patients to hide their syphilis diagnosis due to the severe stigma associated with the disease. References from prominent figures from the 18th to the 20th centuries reveal an apparent debate within the medical community that lamented prioritizing patient privacy over public health, especially for a virulent, disfiguring disease. By mining data sources representing specific locations and broad regions it is suggested that syphilis likely became endemic in the USA sometime between 1810 and 1830. At that point, based on historical references, it appears that syphilis was widespread enough to persist endemically in most communities. A systematic analysis of bioarchaeological sites (28 sites; N=6,611; interments 1600-1944) is conducted to examine the rates and distribution of tertiary syphilis across time and by type of site. Reports demonstrate that no case of the disease has been found from a family, community, or military skeletal collection whereas all institutional skeletal collections report cases of tertiary syphilis with rates ranging from 1 to 19%. This pattern suggests an unrecorded cultural system was in place that culled individuals with tertiary syphilis from mainstream society and placed them in institutions where they were cared for by strangers, perished, and buried in anonymity. This study shows how bioarchaeology can provide significant information on disease and cultural practices not available from other sources.